Análise da proteção de civis na missão multidimensional integrada das Nações Unidas para a estabilização da República Centro-Africana (MINUSCA) - Watanabe, Ana Flávia Pucci Fleury (2021)
This research analyzes the protection of civilians in the United Nations Integrated Multidimensional Mission for the Stabilization of the Central African Republic (MINUSCA). The protection of civilians has become a priority in many peacekeeping missions, which generates discussions in the scope of international relations on the topic and its definition, in addition to the activities to be carried out in search of protection. Considering this discussion, the main concern of this research was to understand how protection has been carried out in the Central African Republic and its due effectiveness. Since this is a country that has been object of few research, that faces many challenges, internal conflicts since its independence and suffers from regional insecurity, it became necessary to implement the United Nations peace operation in 2014. To analyze the effectiveness of the implementation of the priority mandate for the protection of civilians in the country, it was necessary to understand the country's historical and political context, and from studies of official documents, theoretical-conceptual works, specialized literature in the field and a normative framework, the research defined the protection activities among comprehensive and aggressive. In addition, the three dimensions of research analysis were also defined based on the main protection agents in a peacekeeping mission: combatants, peacekeepers and humanitarians.